2012
DOI: 10.1212/wnl.0b013e3182661eca
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Reasoning: A young man with reversible paralysis, cerebral white matter lesions, and peripheral neuropathy

Abstract: A 17-year-old boy experienced 3 consecutive episodes of transient tetraplegia or monoparesis over the course of 5 days, after a week of low-grade fever. He was alert but had dysarthria and diplopia during the attacks. The paresis persisted for 5 to 7 hours and resolved completely.Three years prior, he had presented with a 1-day episode of transient right hemiparesis and dysarthria, and recovered completely without any treatment. At that time, cerebral MRI showed bilateral symmetric confluent hyperintense lesio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 8 publications
1
9
0
1
Order By: Relevance
“…Of the 21 electrophysiological examinations, 14 cases had detectable electrophysiological parameters, and 7 cases had normal laboratory values ( 9 12 , 14 , 15 ). Supplementary Table 1 summarizes 21 electrophysiological examinations in CMTX1 patients with transient central nervous system deficits.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 21 electrophysiological examinations, 14 cases had detectable electrophysiological parameters, and 7 cases had normal laboratory values ( 9 12 , 14 , 15 ). Supplementary Table 1 summarizes 21 electrophysiological examinations in CMTX1 patients with transient central nervous system deficits.…”
Section: Resultsmentioning
confidence: 99%
“…Relapse or recurrent phases may occur 3 months after the first attack. 34 GuillainBarré syndrome is also a monophasic disease, associated with either simultaneous or sequential cerebral demyelination. 79 Symptoms usually reach maximum severity after 4 weeks.…”
Section: Central Nervous System Manifestations Of Cmtx1mentioning
confidence: 99%
“…After Nicholson and Corbett 33 reported abnormal prolonged brainstem auditory evoked responses in a few patients with CMTX1 in 1996, several CMTX cases with transient central nervous system involvement were reported and are now well recognized. In 2012, the authors 34 reported on a young man who presented with transient neurological manifestations, white matter lesions observed by cerebral magnetic resonance imaging (MRI) and atypical CMTX1 features associated with a new-found missense mutation (Asn54Ser) of the connexin 32 gene. As of this writing, 42 articles have been published on PubMed.…”
Section: Central Nervous System Manifestations Of Cmtx1mentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, we identified 47 cases from 38 articles that met the criteria of our systematic review. 11‐48 The gradual selection and exclusion process of the studies is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%